Botched 4 murder - Eaton, J. C. (Joint pseudonym) (Eaton, J. C. (Joint pseudonym) Sophie Kimball mystery., 2018)
A death in her mother's retirement community leads Sophie "Phee" Kimball to investigate a controversial developer and the community's fiercely competitive bocce players.